2014
DOI: 10.1177/1356766713519635
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the meaning of low airfare and satisfaction among leisure air travellers using Malaysian low-cost airlines

Abstract: This study is aimed at understanding the meaning of low airfare and satisfaction from the existing Malaysian low-cost airline travellers. It examines the extent to which low airfare and satisfaction influenced the positive purchase behaviour of travellers. Participant observation and in-depth interviewing were used as data collection methods at the low-cost airline terminals in Malaysia. The findings revealed that low airfare means ‘cheap price paid’, ‘low level of service and performance’ and ‘mode of transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…We have used adapted and modified theoretical & conceptual research model as exhibited in Figure 1; however, most of the factors and items were taken from the previous literature (Metwally, 2013;Chan, 2014;So et al, 2014).…”
Section: The Theoretical and Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used adapted and modified theoretical & conceptual research model as exhibited in Figure 1; however, most of the factors and items were taken from the previous literature (Metwally, 2013;Chan, 2014;So et al, 2014).…”
Section: The Theoretical and Conceptual Modelmentioning
confidence: 99%
“…The results of the previous literature exhibited that organizations that experienced higher customer loyalty were more likely to respond positively to customer complaints (Law, 2017;Estelami, 2000;Fullerton, 2003). The majority of the researchers such as Prentice et al (2017), Davidow (2003), Karande and Magnini (2010), Chan (2014), andSo et al (2014) pointed out interrelated connection among the complaints, response time, quality of response, customer loyalty, company image, and economic aspects. However, more questions still remain to be answered aiming to conjoin resolution perfection, complaint handling, customer satisfaction, customer loyalty and other factors that form a precondition of improving the performance, and economic growth of airline companies.…”
Section: Introductionmentioning
confidence: 98%
“…The cultural dimension has been shown time again to have an effect on passenger expectations in Asian aviation (Gilbert & Wong, 2003). Finally, results from the research did not support H5 (p >0.05), and the relationship between service quality and LCC competitiveness, which is supported by research from Chan (2014) which indicated that LCC passengers are willing to revise their service expectations downward because of the price (Chan, 2014;Kuosuwan, 2015). Thus, the important thing for LCCs is that they determine the expectations of their passengers and meet them (Buaphiban & Truong, 2016).…”
Section: Structural Equation Model (Sem)mentioning
confidence: 79%
“…Otherwise, only a few studies adopted a qualitative method (e.g., interview) to examine the air passengers' evaluations of airline service (Chan, 2014;Westwood et al, 2000). Recently, several researchers have collected and analyzed user generated content (e.g., Tweets) to get an understanding of the airline service factors that make passengers satisfi ed or unsatisfi ed (Liau & Tan, 2014;Misopoulos et al, 2014).…”
Section: Measurement Of Airline Service Qualitymentioning
confidence: 99%